Bioactivation of cinnamic alcohol in a reconstructed human epidermis model and evaluation of sensitizing potency of the identified metabolites - Ndreu, Lorena; Carlsson, Josefine; Ponting, David J.; Niklasson, Ida B.; Stéen, E. Johanna L.; McHugh, Lukas; O’Boyle, Niamh M.; Luthman, Kristina; Karlberg, Ann-Therese; Karlsson, Isabella (Frontiers in Toxicology, 2024)
BackgroundCinnamic alcohol is a natural compound, widely used in fragrances, which can cause allergic contact dermatitis. Cinnamic alcohol lacks intrinsic reactivity and autoxidation or metabolic activation is necessary for it to act as a sensitizer.MethodsBioactivation of cinnamic alcohol was explored using human liver microsomes, human liver S9 and SkinEthic™ Reconstructed Human Epidermis. A targeted multiple reaction monitoring mass spectrometry method was employed to study and quantify cinnamic alcohol along with eight potential phase I or phase II metabolites. The reconstructed human epidermis model, treated with cinnamic alcohol, was also analyzed with a non-targeted high-resolution mass spectrometry method to identify metabolites not included in the targeted method.ResultsTwo metabolites identified with the targeted method, namely, pOH-cinnamic alcohol and pOH-cinnamic aldehyde, have not previously been identified in a metabolic in vitro system. Their reactivity toward biologically relevant nucleophiles was investigated and compared to their sensitizing potency in vivo in the murine local lymph node assay (LLNA). According to the LLNA, the pOH-cinnamic alcohol is non-sensitizing and pOH-cinnamic aldehyde is a moderate sensitizer. This makes pOH-cinnamic aldehyde less sensitizing than cinnamic aldehyde, which has been found to be a strong sensitizer in the LLNA. This difference in sensitizing potency was supported by the reactivity experiments. Cinnamic sulfate, previously proposed as a potential reactive metabolite of cinnamic alcohol, was not detected in any of the incubations. In addition, experiments examining the reactivity of cinnamic sulfate toward a model peptide revealed no evidence of adduct formation. The only additional metabolite that could be identified with the non-targeted method was a dioxolan derivative. Whether or not this metabolite, or one of its precursors, could contribute to the sensitizing potency of cinnamic alcohol would need further investigation.DiscussionCinnamic alcohol is one of the most common fragrance allergens and as it is more effective to patch test with the actual sensitizer than with the prohapten itself, it is important to identify metabolites with sensitizing potency. Further, improved knowledge of metabolic transformations occurring in the skin can improve prediction models for safety assessment of skin products.